KETAHANAN BAJA ASTM A36 TERHADAP PENGUJIAN TARIK DAN BENDING DENGAN PROSES PENGELASAN SMAW DAN METALOGRAFI - Aditya Faza Al Faridzi; Ponidi (Universitas Muhammadiyah Surabaya, 2024)
In the welding process, the parts to be welded receive local heat, thermal expansion occurs, even though the cold parts do not change, this causes structural stress and structural changes can occur. Therefore, the choice of electrode type significantly influences the tensile and bending stresses as well as changes in structural content. Based on the analysis carried out, the E6013 type electrode has the lowest tensile stress value, namely 455.8707 N/mm². Meanwhile, the highest average tensile stress on the E7016 type electrode reached a tensile value of 561.47535 N/mm². The highest Bending Stress value was 162.95 (N/mm²) for the E7016 electrode and 155.85 (N/mm²) for the E6013 electrode. and in the E6013 microstructure element the carbon C content is 6.92% and in the E7016 sample the carbon C element content is 3.61%. A low hydrogen content really prevents oxidation during welding, because when steel has a high oxygen content, the tensile stress and yield when moving during welding will be reduced. Keywords: Electrodes, Tensile Test, Bending Test, Microstructure, Weld Defects.